I've started reading through a pre-calculus textbook for self-study and came across this problem in the second chapter: $$(x-2)^3-(x-2)^2$$ The final answer is $(x-2)^2(x-3)$

Everywhere I look but I have no idea how it comes to that. Binomial expansion was mentioned on one site but the binomial theorem appears in a later chapter. What is the method/methods used to factor this expression?

  • 1
    $\begingroup$ Let $\ y = x\!-\!2.\ $ Then it is $\ y^3 - y^2 = y^2(y - 1) = (x\!-\!2)^2 (x\!-\!2 - 1)\ \ $ $\endgroup$ – Bill Dubuque Jun 25 '15 at 22:47

Use the distributive property: $$ab-ac=a(b-c)$$ Here, we have $$a=(x-2)^2\qquad b=(x-2)\qquad c=1$$ Thus $$(x-2)^3-(x-2)^2=(x-2)^2((x-2) -1)=(x-2)^2(x-3)$$

  • $\begingroup$ Thank you! Now it makes sense. $\endgroup$ – dantastic Jun 25 '15 at 23:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.